THE SISAL FIBER (Agave Sisalana) ALKALIZATION EFFECTS ON THE IMPACT STRENGTH OF FIBER REINFORCED ACRYLIC RESIN - Benni Benyamin; Musri Amurwaningsih; Wirda Yunita Darwis (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Acrylic resins, as dentistry materials, were widely used as artificial tooth based because of flexibily, easily obtained, inexpensive, and the most significant reason was biocompatible. Acrylic resin itself had a deficiency of brittle and easy fracture. One solution to overcome these shortcomings was to add sisal fibers to acrylic resins known as Fiber Reinforced Acrylic Resins (FRAR). The purpose of this research was to know the effect of sisal fiber addition to the impact strength of FRAR.Methods: Post-test-only control group design was used as laboratory experimental. Total used sample was 32 acrylic resin plats hot cured with size 55x10x10 mm. Experiment group was divided into two groups, one group with non-alkalization, and another group with alkalization. Impact strength was tested by universal testing machine (UTM).Results: Impact strength highest avarage was on alkalization group, with number 0.0214 J/mm2 and the lowest was on non-alkalization group, with number 0.0145 J/mm2. The result was tested by independent T-Test with significant number was 0,000 (P<0,05) which means there were a significant effect of impact strength FRAR between groups.Background: Acrylic resins, as dentistry materials, were widely used as artificial tooth based because of flexibily, easily obtained, inexpensive, and the most significant reason was biocompatible. Acrylic resin itself had a deficiency of brittle and easy fracture. One solution to overcome these shortcomings was to add sisal fibers to acrylic resins known as Fiber Reinforced Acrylic Resins (FRAR). The purpose of this research was to know the effect of sisal fiber addition to the impact strength of FRAR.Methods: Post-test-only control group design was used as laboratory experimental. Total used sample was 32 acrylic resin plats hot cured with size 55x10x10 mm. Experiment group was divided into two groups, one group with non-alkalization, and another group with alkalization. Impact strength was tested by universal testing machine (UTM).Results: Impact strength highest avarage was on alkalization group, with number 0.0214 J/mm2 and the lowest was on non-alkalization group, with number 0.0145 J/mm2. The result was tested by independent T-Test with significant number was 0,000 (P<0,05) which means there were a significant effect of impact strength FRAR between groups.Conclusion: The impact strength of FRAR increased after alkalization treatment The impact strength of FRAR increased after alkalization treatment